THE IMPLEMENTATION OF ORGANISTIC THINKING PRINCIPLES IN PAVEL RIVILIS’S ORCHESTRAL TRANSCRIPTION OF J.S. BACH’S CIACONNE - PÎSLARI SNEJANA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2019)
This article focuses on the analysis of several peculiarities of Pavel Rivilis’s organistic thinking in the orchestral transcription of J.S. Bach’s Ciaconne, principles that are implemented by the composer through the use of slow and rare timbre changes; contrastive comparison of the orchestral masses and "special registers’ disposition”, expressed in a conventional separation of instruments into groups of labial and reed instruments.